Prolonged use of wind or brass instruments does not alter lung function in musicians - Fuhrmann, A.; Franklin, P.; Hall, Graham (Elsevier Ltd, 2011)
Purpose: Respiratory function impacts on musical expression for wind/brass (W/B) musicians. Investigation of musicians’ respiratory health to date has rarely progressed further than assessments of flow limitation through spirometry. This study aimed to compare W/B musicians’ respiratory function to a non-wind/brass (NW/B) group with a comprehensive respiratory function assessment. Methods: Non-smoking, non-asthmatic participants aged 18–60 years completed a respiratory health questionnaire followed by spirometry, static lung volumes, respiratory mechanics, using forced oscillations, gas transfer and airway responsiveness (AR). Measurements were compared between participant groups using T-tests and linear regression modelling. Results: Data from 102 participants (55 W/B musicians and 47 NW/B subjects) were included in the analysis. There were no differences between the two groups for any spirometry or lung volume outcomes, with the exception of RV/TLC which was decreased among W/B musicians (p = 0.03). Measures of gas transfer and AR were similar between participant groups. Resistance at 6 Hz, measured by forced oscillation, was increased among W/B musicians compared to NW/B musicians (p = 0.02) but reactance at 6 Hz was similar between the groups (p = 0.10). Conclusions: The results suggest that W/B musicians’ do not have altered respiratory function when compared to a non-musical control group. However, increased Rrs6 may indicate inflammatory, remodelling or other pathophysiological processes associated with W/B playing. Although the difference between groups was small it warrants further investigation.